CONCENTRACIONES FOSILÍFERAS ORDOVÍCICAS EN LAS FORMACIONES ACOITE y SEPULTURAS, CORDILLERA ORIENTAL JUJEÑA. ANÁLISIS TAFONÓMICO y PALEOECÓLOGICO (Ameghiniana, 2014)
"A detailed taphonomic analysis of trilobite-dorninated fossil concentrations was performed in the middle-upper part of the Acoite and Sepulturas Formations at the western flank of Cordillera Oriental, Jujuy Province. Based on biostratinornic índices and fabric of the concentrations, three types of bioclastic deposits have been recognized: (1) bidimensional bioclastic deposits, (2) thin and closely packed bioclastic deposits, and (3) tabular bioclastic deposits with complex microstratigraphy. Bidimensional bioclastic deposits were formed under null sedimentation rates. Two grades have been distinguished according to the effects of physical processes: grade ""a"" in which primary biogenic processes were obliterated, and grade ""b"" interpreted as biogenic concentrations subsequently reworked. Thin and closely packed bioclastic deposits are formed under low rates of detritial sedimentation and high rates of autochthonous hard part input, alternating with episodic increments in clastic supply. Both types of bioclastic deposits reflect diastemic interruptions during the aggradational process of the stratigraphic record. Despite the ecological shifts related to substrate consistency and turbidity levels, no significant faunal replacement was achieved during the development of these deposits. The tabular bioclastic deposit with complex microstratigraphy accounts for a shallowing-up cycle in an otherwise distal shelf environment. The complex internal nature indicates condensation of the palaeontologic and sedimentologic record. The faunal turnover is interpreted as an example of community tracking in response to sea level changes. From a palaeoecological viewpoint trilobite associations display low levels oftirne-averaging. They were only slightly affected by short term environmental fluctuations, showing a long term trend of ecologic persistence."